Heterotopic ossification (HO) prophylaxis in total hip arthroplasty (THA): A systematic review of level I and level II evidence since 2000 - Troy B. Puga; McKenna W. Box; Vincent M. Dieu; Charles R. Marchese; John T. Riehl (Bone Reports)
Introduction: Heterotopic ossification (HO) is a somewhat common occurrence after total hip arthroplasty (THA), particularly with certain approaches. This complication can be detrimental to the success of the surgical outcome. Indomethacin and radiotherapy remain common treatment modalities; however, no true gold-standard treatment is universally agreed upon. This study aims to evaluate Level I and Level II evidence for treatment practices of HO prophylaxis since 2000. Methods: To evaluate HO prophylaxis in total hip arthroplasty, a search was conducted across MEDLINE/Pubmed, Cochrane, and Embase databases using keywords and Medical Subject Heading (MeSH) terms. Titles and abstracts were screened for eligibility for inclusion criteria. Full texts were screened and included if they met eligibility criteria. Results: HO chemical prophylaxis was more effective than no HO prophylaxis, except for aspirin. Multiple NSAIDs showed equivalence and better side effect profiles than indomethacin. No one superior NSAID was found, and numerous modalities showed efficacy. The most effective dosages of radiation therapy and combination therapy remain unclear. Additionally, both etidronate and salmon calcitonin showed benefit in preventing HO in one study each. Conclusion: Radiation, NSAIDs, and combination therapy all showed efficacy as HO prophylaxis modalities. HO prophylaxis treatment and modalities should be guided upon patient and surgical factors such as surgical approach, side effects and tolerability of modalities, comorbidities, and available facility resources to optimize the prevention of HO.Level of evidence: Level IV Therapeutic.